2018
DOI: 10.1167/iovs.17-23685
|View full text |Cite
|
Sign up to set email alerts
|

Contact Lens-Associated Dry Eye Disease: Recent Advances Worldwide and in Japan

Abstract: Contact lens wearers complain of various types of contact lens discomfort (CLD), which may result in the discontinuation of contact lenses. CLD is often associated with dry eye disease. A contact lens divides the tear film into two layers: the pre-and post-lens tear film. This change leads to instability of the pre-lens tear film, thinning of pre-and post-lens tear film thickness, and increased friction between the contact lens and the ocular surface. The Japanese Dry Eye Society recommends the diagnosis of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 56 publications
6
73
0
Order By: Relevance
“…35 Any homeostatic imbalance caused by ocular surface conditions, such as dry eye or meibomian gland dysfunction, can become exacerbated by a contact lens and lead to contact lens discomfort or contact lens-induced dry eye. 23,36 This issue as it relates to contact lens dropout has been specifically analyzed by Giannaccare et al (2016) via a retrospective analysis (n = 87). 37 The authors found that compared to controls, subjects who had discontinued contact lens wear had lower/worse tear break up time and Schirmer test values, and higher/worse ocular surface disease index (OSDI) and corneal staining scores.…”
Section: Ocular Surface Factorsmentioning
confidence: 99%
“…35 Any homeostatic imbalance caused by ocular surface conditions, such as dry eye or meibomian gland dysfunction, can become exacerbated by a contact lens and lead to contact lens discomfort or contact lens-induced dry eye. 23,36 This issue as it relates to contact lens dropout has been specifically analyzed by Giannaccare et al (2016) via a retrospective analysis (n = 87). 37 The authors found that compared to controls, subjects who had discontinued contact lens wear had lower/worse tear break up time and Schirmer test values, and higher/worse ocular surface disease index (OSDI) and corneal staining scores.…”
Section: Ocular Surface Factorsmentioning
confidence: 99%
“…Alternative environmental factors, like poor ergonomics, improper lighting, glare, cut wetness in air-conditioned rooms, 28 are all tributary factors for worsening of those symptoms. Uncorrected refractive errors, 29 contact-lens wearers, 30 people with a history of ocular illnesses, 31 diabetics, 32 female gender, 33 and autoimmune diseases are at risk for the development of more and severe symptoms than their age-matched counterparts.…”
Section: Why/how Do Screens Cause Eyestrain?mentioning
confidence: 99%
“…Decreased tear film stability as measured with tear film BUT occurs with long term use of contact lenses stability. In a recent study, ocular discomfort and other dry eye symptoms were present in contact lens wearers 20 . The reason might be the daily wearing time of soft contact lens induced hypoxia and caused disturbances in pre corneal tear film stability.…”
Section: Discussionmentioning
confidence: 93%